PENGARUH WAKTUPADA PENYULINGAN MINYAK ADAS (Fennel Oil) DARI BIJI DAN DAUN ADAS DENGAN METODE UAP DAN AIR - Adi Hendra Prakosa; Inda Dewi Pamungkas; Diyono Ikhsan (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
Fennel oil is an oil produced from the fennel plant (Foeniculum vulgare) through a process of distillation. In this study, using the method of steam and waterdistillation which vapor source was distilled in a kettle. The purpose of the distillation  process is to obtain essential oils from aromatic plants which has contains oil that are difficult to extraction in normal conditions. The benefits of this process is to obtain fennel oil and by-products such as the distillation residue can be dried as fodder ransom. Fennel oil is known as one of the allround flavouring agent because it has a distinctive aroma, attractive and widely used in the cosmetic industry for perfumes such as soaps, perfumes, detergents and others.In this study there are two kinds of variables, ie variables and variables remain unchanged. For fixed variables consist of: a pressure of 1 atm and a temperature of 100oC, while changing variables include: distillation time and type of material. In the research,the process of disstilation the was conducted for 2, 3, 4, 5 and 6 hours for each type of material that is part of the seeds and leaves. Raw materials obtained from the Bandungan, Ungaran, Central Java. The observations made is the determination of the yield, organoleptic testing, refractive index and anetol levels of fennel oil produced.Our results, for the seeds produces the highest yield of 0.607% on refining for 4 hours and leaves to produce the highest yield of 0.27% on refining sub 4 hours. According organoleptic yellow anise oil and fennel characteristic odor. Refractive index obtained from the studies ranged from 1.5200 to 1.5330.Levels anetol analysis using GC, the seeds obtained at 54.4873% and in the leaves only 10.9032%.